Dorling Kindersley Animal Encyclopedia - Dorling Kindersley; Created by: Bob Gordon, Edited by: Charlotte Stock, Designed by: SuzanneTuhrim (New York Dorling Kindersley Publishers, 2006)
Provides information about the physical characteristics, habits, and behavior of such animals as hedgehogs, peacocks, penguins, salamanders, and snakes.
Colour Illustration
Include Index
Keywords: Animals